Prevalence and Factors Associated With Suicidal Ideation Among Adult Eritrean Refugees in Northern Ethiopia - Teferi Gebru Gebremeskel; Teferi Gebru Gebremeskel; Mulaw Berhe; Tadis Brhane Tesfahunegn; Hailay Abrha Gesesew; Hailay Abrha Gesesew; Paul R. Ward (Frontiers Media S.A., 2022)
BackgroundThe present study assessed the prevalence of and factor associated with suicidal ideations among adult Eritrean refugees in Tigray, Ethiopia.MethodsA community-based cross-sectional study was carried out among 400 adult refugees living in the Mai-Aini refugee camp in Tigray, Northern Ethiopia from September 2019 to May 2020. The response variable was suicidal ideation and was measured using World Mental Health (WMH) Survey Initiative Version of the World Health Organization Composite International Diagnostic Interview. We applied bivariate and multivariate logistic regression to determine predictors for suicide ideations. Odds ratios and p-values were determined to check the associations between variables, and a p-value <0.05 was considered as a cut-off for statistical significance.ResultsThe prevalence of suicidal ideations was 20.5% (95% CI: 16.4%, 24.5%). Having previous history of trauma [AOR = 2.3, 95% CI: 1.4, 4.5], a history of chronic illness [AOR = 2.9, 95% CI: 1.3, 6.5], a family history of mental disorder [AOR = 3.08, 95% CI: 1.3, 7.06], and history of post-traumatic stress disorder [AOR = 5.7, 95% CI: 2.8, 11.5] were significantly associated with suicidal ideations.ConclusionsThis study showed that during the stay in the refugee camp, there was a high prevalence of suicide ideations compared to the prevalence of suicide ideations among the general populations of Ethiopia, Europe, and China, and the lifetime pooled prevalence across 17 countries. Having previous history of trauma, a history of chronic illness, a family history of mental disorder, and history of post-traumatic stress disorder were the factors statistically associated with the suicidal ideation.